ANTIBACTERIAL ACTIVITY of CRUDE METHANOLIC LEAVES EXTRACT of Xylocarpus granatum AGAINST BACTERIAL FISH PATHOGEN Staphylococcus epidermidis - Ummi Mardhiah Batubara; Madyawati Latief; Winda Dwi Setiawati (Berkala Perikanan Terubuk, 2021)
Sumatera is one of the largest mangrove areas in Indonesia. One of the mangrove plants that have the potential as a drug and has been used traditionally is Xylocarpus granatum. This study was conducted to determine the influence of methanol extract from leaf X. granatum in inhibiting the growth of Staphylococcus epidermidis. Extraction of leaf X. granatum is done by the maceration method using methanol solvent. Test resistance of methanol extracts from the leaves of X. granatum is performed by a method of diffusion discs. Measurement of antibacterial activity is carried out with several treatments i.e. the negative control (aquadest), positive control (Chloramphenicol), and several different extract concentrations of 25ppm, 50ppm, 75ppm, and 100ppm. The value of the antibacterial activity is then analyzed further using ANOVA and the Dunn test. The results showed that the leaves extract X. granatum extracted using a methanol solvent contained active phytochemicals compounds such as steroids, saponins, tannins, and phenols. The test results of each extract concentration showed a significant influence on the slow growth of S. epidermidis, characterized by the formation of a clear zone around the disc. The highest antibacterial activity is shown at a concentration of 25ppm with an antimicrobial index value of 3,55 which is categorized as a strong antibacterial response.